Phenotypic Diversification Of Terrestrial Cyanobacteria From Selected Habitats On Signy Island, South Orkney Islands, Antarctica - Radzi, Ranina Alya Mohamad (2020)
A floristic study was conducted on cyanobacteria from terrestrial habitats in Signy Island (60.7170° S, 45.6000° W), South Orkney Islands during the expedition of British Antarctic Survey (BAS) in austral summer of 2015/2016. Samples were collected following the previous 120 locations that was provided by Broady (1979). Thirty seven out of 120 collection sites established by Broady (1979) were successfully obtained and compared in this study. Changes in the cyanobacteria community at sites previously studied by Broady (1979) will provide excellent baseline information on the status of Antarctic terrestrial cyanobacteria diversity and dispersal. It is crucial to understand how the Antarctic life form is responding to current environmental change and what the continent was like in the past. This study has integrated traditional morphological and modern molecular taxonomic approaches providing new insights into the taxonomy of Antarctic cyanobacteria. Seventeen morphospecies belonging to 14 genera; Chamaesiphon, Cyanosarcina, Desmonostoc, Leptolyngbya, Microcoleus, Nodosilinea, Nostoc, Oscillatoria, Phormidium, Phormidesmis, Pseudanabaena, Synechocystis, Trichocoleus and Wilmottia have been recorded with robust descriptions by using streaking and most probable number techniques. Ten morphospecies recorded were similar to records by Broady (1979). Seven of the morphospecies; Leptolyngbya cf. subcapitata, Nodosilinea signiensis, Oscillatoria cf. subsala, Phormidium uncinatum, Trichocoleus cf. hospitus, Wilmotia murrayi M1 and Wilmottia murrayi M2 are new records for Signy Island.